First International Conference on Integration and Commercialization of Micro and Nanosystems, Parts a and B 2007
DOI: 10.1115/mnc2007-21385
|View full text |Cite
|
Sign up to set email alerts
|

Research on Micro Accelerometer Array

Abstract: In a physical process, there might be more than one acceleration to be measured, but a micro accelerometer of a certain testing range can hardly satisfy the measurement requirement. In this paper, a micro accelerometer array with four testing ranges, namely, 0∼100g, 0∼500g, 0∼1,000g and 0∼2,000g, is designed and fabricated. In addition to the design and fabrication process, the protection for the array elements on the condition of overload is described in detail. From the static and dynamic measurement results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The array-type pressure sensor system comprises several pressure sensors with different ranges; therefore, it can achieve high linearity and sensitivity within the hybrid composite range and to meet the accurate radiosonde pressure measurement in the full range from 0 to 100 kPa. At present, there have been studies about pressure sensor array [ 5 , 9 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. For instance, Sugiyama et al [ 18 ] reported a 32 × 32 (1k)-element silicon pressure sensor array consisting of piezoresistive elements and CMOS processing circuit, and the array can provide two-dimensional pressure distribution tests for tactile image detection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The array-type pressure sensor system comprises several pressure sensors with different ranges; therefore, it can achieve high linearity and sensitivity within the hybrid composite range and to meet the accurate radiosonde pressure measurement in the full range from 0 to 100 kPa. At present, there have been studies about pressure sensor array [ 5 , 9 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. For instance, Sugiyama et al [ 18 ] reported a 32 × 32 (1k)-element silicon pressure sensor array consisting of piezoresistive elements and CMOS processing circuit, and the array can provide two-dimensional pressure distribution tests for tactile image detection.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, three different types of sensors (different sensitivities and ranges), featuring a diaphragm thickness of 3 μm and diaphragm sizes of 500 μm, 700 μm, and 900 μm, have been fabricated and attached to the printed circuit board (PCB) with a spacing of 6 mm to form the array, which is mounted flush with the measurement surface. Xiong et al [ 21 ] designed a composite-range micro accelerometer array consisting of four piezoresistive micro accelerometers with the range of 100 g, 500 g, 1000 g, and 2000 g, respectively. The composite-range micro accelerometer has a good linearity and the problem that the acceleration may have a relatively large dynamic range in the same physical process is solved, thus it can accurately measure the acceleration values that cover the high and low range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation